(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Nasal carriage of MRSA among hospital stuff act as a source of endogenous infection and becomes a source for hospital and community acquired infection. The study was conducted to determine the rate antibiotic resistance pattern of nasal carriage of MRSA among the hospital stuff of Sir Salimullah Medical College and Mitford Hospital, Dhaka. Pre moistened nasal swabs from hospital stuff (doctor, nurses, lab technicians and other helping stuff were obtained. These swabs were inoculated into Blood agar and Mannitol salt agar media. Antibiogram was done by modified Kirby Bauer disc diffusion method. MRSA were detected by oxacillin and cefoxitin disc diffusion method. The resistance was confirmed by MIC of oxacillin agar dilution method. Out of 142 samples 34 strains of Staphylococcus were isolated among them 07 (4.93%) were MRSA and 27 (19.01%) were MSSA. The carriage rate of MRSA was higher among nurse than other healthcare provider. Nasal carriage of MRSA is responsible for spreading infection from healthcare personnel to normal individual. So, regular screening of carrier is required from prevention of hospital acquired infection. Bangladesh J Med Microbiol 2017; 11 (2): 17-19